2018
DOI: 10.1002/uog.17496
|View full text |Cite
|
Sign up to set email alerts
|

Population trends in prenatal detection of transposition of great arteries: impact of obstetric screening ultrasound guidelines

Abstract: Substantial improvement in the prenatal detection of d-TGA has been observed in Alberta over the past few years, owing to improved screening of cardiac outflow tracts on routine obstetric ultrasound examination in otherwise healthy pregnancies, and has been temporally associated with updated obstetric ultrasound guidelines suggesting that these contributed to optimized screening of affected pregnancies. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…The introduction of the 3VV as a mandatory plane is an example of a successful change with a direct effect. Recently, Ravi et al reported comparable DR for TGA only, with a gradual improvement following guideline changes. Our study differs from Ravi et al as our data show the strength of the 3VV in itself on TGA detection and the fact that the DRs for TGA change immediately after the introduction of 3VV in a centrally organized screening program.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The introduction of the 3VV as a mandatory plane is an example of a successful change with a direct effect. Recently, Ravi et al reported comparable DR for TGA only, with a gradual improvement following guideline changes. Our study differs from Ravi et al as our data show the strength of the 3VV in itself on TGA detection and the fact that the DRs for TGA change immediately after the introduction of 3VV in a centrally organized screening program.…”
Section: Discussionmentioning
confidence: 93%
“…The key to the diagnosis in ToF cases with a relatively normal sized pulmonary artery is the more anterior positioned aorta in the 3VV. This aspect of the 3VV did not gain much attention in the past, probably because most training programs and studies were focused on gaining higher DRs for TGA . We decided to train our region on this aspect in the last 3 years of the studied period and called the normal spatial relationship and positioning of pulmonary artery, aorta, and vena cava superior in the 3VV the “Leiden line.” The presented data of this study are, however, far too small to prove the help of this training tool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, whereas implementation of obstetrical screening guidelines boast a prenatal diagnosis of transposition approaching 80% in North America, the findings worldwide are far more sobering. [12][13][14] We must acknowledge that for many developing countries, baffling as it seems, the atrial switch has never left the front page of Vogue. 15 Until earlier diagnosis (and balloon atrial septostomy) is more broadly available worldwide, the tireless pursuit of perfection in the atrial switch will continue to represent a professional mandate.…”
mentioning
confidence: 99%